Method for preparing cellulose nanocrystals by utilizing pulsed electric field to assist ammonium persulfate oxidation

Through pulsed electric field pretreatment and ammonium persulfate oxidation methods, the problems of low yield and complex processing of cellulose nanocrystal preparation are solved, and efficient and low-cost cellulose nanocrystal preparation is achieved, which improves yield and dispersion stability. Provides more functional approaches.

CN119241731APending Publication Date: 2025-01-03SOUTH CHINA UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411494322.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing cellulose nanocrystal preparation methods have problems such as low yield, long processing time, and high energy consumption, and the traditional carboxylation process is complex and costly.

Method used

Cellulose nanocrystals were prepared by pulsed electric field (PEF) pretreatment combined with ammonium persulfate (APS) oxidation method. The specific surface area of ​​cellulose is improved through pulsed electric field treatment, the accessibility of chemical reagents is increased, and the yield of nanocrystals is improved. , and obtain highly dispersed and stable cellulose nanocrystals by low temperature freeze-drying or spray-drying.

Benefits of technology

It significantly improves the yield of cellulose nanocrystals, reduces production costs, reduces harmful substance residues, provides higher carboxyl content and dispersion stability, and provides more ways to the functional application of cellulose nanocrystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241731A_ABST
    Figure CN119241731A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing cellulose nanocrystals under the assistance of a pulsed electric field. The method comprises the following steps: treating cellulose powder through a pulsed electric field, controlling the intensity of the electric field to be 10-30kV / cm, carrying out suction filtration and drying after treatment, adding an ammonium persulfate solution into the obtained solid for oxidative degradation, and centrifuging to prepare the cellulose nanocrystal. The method is green and low in toxicity, and the yield of the cellulose nanocrystal is remarkably improved under the action of the pulsed electric field. Besides, the prepared cellulose nanocrystal has higher dispersion stability, excellent specific surface area, no harmful substance residue and higher carboxyl content, more chemical ways are provided for further modification of the nanocellulose, and a new method is provided for pretreatment of preparation of the cellulose nanocrystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose nanocrystal preparation, and relates to a method for preparing cellulose nanocrystal, and specifically to a method for preparing carboxylated cellulose nanocrystal by utilizing pulsed electric field (PEF)-assisted ammonium persulfate (APS) oxidation. Background Art

[0002] Nanocellulose refers to cellulose in nanomaterials in which at least one dimension is at the nanoscale (1-100nm), and the nanomaterial can be dispersed in water to form a stable suspension of cellulose crystals. According to the morphology, particle size and source of nanocellulose, nanocellulose is divided into the following three categories: ① cellulose nanofiber (CNF), ② cellulose nanocrystals (CNC) and ③ bacterial nanocellulose (BNC). CNC is also called nanocrystalline cellulose, cellulose nanowhiskers and crystalline nanocellulose. CNC is rod-shaped or whisker-shaped, with a length of 100-500nm and a diameter of 2-20nm. In addition, it has some excellent properties, such as a large specific surface area (~150m 2 / g), high crystallinity (>70%), high tensile strength (7500MPa) and large aspect ratio (~70). Therefore, CNC can be used in various industrial fields, such as healthcare, electronics, construction, food packaging, 3D printing, polymer composites, etc.

[0003] Cellulose nanocrystals are usually produced by acid hydrolysis or chemical oxidation combined with pretreatment. However, these methods have some disadvantages, such as low cellulose nanocrystal yield (30% to 50%), long processing time, high energy consumption, etc. Summary of the invention

[0004] The present invention aims to provide a novel pretreatment method for the preparation of cellulose nanocrystals, wherein cellulose powder is pretreated with a pulse electric field (PEF) and then oxidized with ammonium persulfate to obtain cellulose nanocrystals. The method is green and low-toxic, and the yield of cellulose nanocrystals is significantly increased under the action of the pulse electric field. In addition, the prepared cellulose nanocrystals have high dispersion stability, excellent specific surface area, no harmful substances remaining, and a high carboxyl content, providing more chemical pathways for further modification of nanocellulose.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for preparing carboxylated cellulose nanocrystals by using pulsed electric field-assisted ammonium persulfate (APS) oxidation comprises the following steps:

[0007] (1) crushing a bleached fiber pulp sheet to obtain cellulose powder;

[0008] (2) preparing a suspension of cellulose powder with deionized water at a solid-liquid ratio of 1:50-1:100, stirring evenly, connecting a peristaltic pump, adjusting the flow rate and removing bubbles, allowing the sample to fully flow through the pulse electric field treatment chamber, performing pulse electric field treatment, and then filtering and drying to obtain treated cellulose; the pulse electric field treatment conditions are: field strength 10-30 kV / cm, frequency 50-300 Hz, pulse width 8-10 μs, and treatment time 5-20 min;

[0009] (3) adding APS into water and dissolving it to form an APS aqueous solution;

[0010] (4) adding the PEF-treated cellulose to the APS solution for full reaction;

[0011] (5) The suspension after the reaction is washed to neutrality by centrifugation to separate the cellulose nanocrystal dispersion, which is then freeze-dried or spray-dried to obtain solid cellulose nanocrystals.

[0012] Preferably, in step (1), the bleached fiber pulp is one or a mixed bleached pulp of microcrystalline cellulose, bleached bagasse pulp, bleached lychee peel pulp, bleached wood pulp, bleached straw pulp, bleached cotton pulp, bleached bamboo pulp, etc.

[0013] Preferably, in step (1), the bleached fiber pulp is crushed and then passed through a 200-mesh sieve to obtain cellulose powder.

[0014] In step (2), the mass percentage concentration of the ammonium persulfate APS aqueous solution is 15% to 21%.

[0015] Preferably, in step (2), the material-liquid ratio is 1:60-1:80 g / ml.

[0016] Preferably, in step (2), the pulse electric field treatment conditions are: field strength 10-25 kV / cm, preferably 15-20 kV / cm, frequency 200-300 Hz, pulse width 8-10 μs, and treatment time 10-15 min.

[0017] Preferably, in step (3), the APS concentration is 15% to 25%.

[0018] Preferably, in step (3), the flow rate of the peristaltic pump is 200-300 ml / min.

[0019] Preferably, in step (4), the reaction time is 10 to 16 hours and the reaction temperature is 55 to 90°C.

[0020] Preferably, in step (5), the washing is performed by repeatedly adding deionized water and centrifuging until neutral, and the centrifugal speed is 6000-7000 rpm / min.

[0021] Compared with the prior art, the advantages of the present invention are:

[0022] (1) The pulse electric field treatment technology used in the present invention is a green physical processing method that is efficient and environmentally friendly, can be used for large-scale production, and is widely used in the food industry. It is a new pretreatment method for preparing cellulose nanocrystals.

[0023] (2) The present invention adopts pulse electric field pretreatment, which increases the specific surface area of ​​cellulose through a relatively short period of pulse electric field treatment, thereby improving the accessibility of cellulose to chemical reagents and greatly improving the yield of cellulose nanocrystals.

[0024] (3) The cellulose nanocrystals prepared by the present invention have a high carboxyl content, which reduces the additional processes and drug consumption required for the traditional nanocellulose carboxylation, greatly reduces the cost, and provides more means for the further functionalization and wide application of cellulose nanocrystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the cellulose nanocrystal yield of Comparative Example 1, Comparative Example 2 and Examples 2, 5, 7, and 8;

[0026] Figure 2 The cellulose scanning electron microscope images of Comparative Example 1 and Examples 5 and 7 are shown;

[0027] Figure 3 Graph showing the carboxyl content of cellulose nanocrystals of Comparative Example 1, Comparative Example 2 and Examples 2, 5, and 7. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Comparative Example 1

[0030] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0031] (2) Add cellulose powder to an APS solution having a mass percentage concentration of 18 wt %, and react at 70° C. for 14 h to obtain a reaction suspension.

[0032] (3) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0033] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in this comparative example 1 is 51.67%.

[0034] Comparative Example 2

[0035] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0036] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 30 kV / cm, frequency 500 Hz, pulse width 15 μs, treatment time 20 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0037] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 18 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0038] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0039] Comparative Example 2 is a control for electric field treatment conditions. According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Comparative Example 2 is 48.77%, which is 5.61% lower than the cellulose nanocrystal yield without PEF treatment.

[0040] Example 1

[0041] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0042] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 10 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0043] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 15 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0044] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0045] According to the calculation method of the cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 1 was 56.11%, which was 8.59% higher than that of cellulose nanocrystals not treated with PEF.

[0046] Example 2

[0047] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0048] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 10 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0049] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 18 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0050] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0051] According to the calculation method of the cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 2 was 58.26%, which was 12.75% higher than that of cellulose nanocrystals not treated with PEF.

[0052] Example 3

[0053] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0054] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 10 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0055] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 21 wt%, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0056] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0057] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Implementation 3 was 55.65%, which was 7.7% higher than that of cellulose nanocrystal without PEF treatment.

[0058] Example 4

[0059] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0060] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 15 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0061] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 15 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0062] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0063] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 4 was 60.52%, which was 17.13% higher than that of cellulose nanocrystal without PEF treatment.

[0064] Example 5

[0065] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0066] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 15 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0067] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 18 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0068] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0069] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 5 was 64.45%, which was 24.73% higher than that of cellulose nanocrystal without PEF treatment.

[0070] Example 6

[0071] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0072] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 15 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0073] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 21 wt%, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0074] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0075] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 6 was 59.33%, which was increased by 14.82% compared with the cellulose nanocrystal yield not treated with PEF.

[0076] Example 7

[0077] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0078] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 20 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0079] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 18 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0080] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0081] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 7 was 58.52%, which was 13.3% higher than that of cellulose nanocrystals not treated with PEF.

[0082] Example 8

[0083] (1) The bleached fiber pulp is crushed through a 200-mesh sieve to obtain cellulose powder.

[0084] (2) Dispersing cellulose powder in water to prepare a suspension, pumping it into a pulsed electric field treatment chamber, the pulsed electric field treatment conditions are: field strength 25 kV / cm, frequency 250 Hz, pulse width 10 μs, treatment time 10 min, filtering and drying to obtain cellulose solids after pulsed electric field treatment.

[0085] (3) The cellulose obtained in (1) was added to an APS solution having a mass percentage concentration of 18 wt %, and the mixture was reacted at 70° C. for 14 h to obtain a reaction suspension.

[0086] (4) Deionized water was repeatedly added to the reaction suspension and washed by centrifugation until it became neutral to obtain a cellulose nanocrystal suspension, which was then freeze-dried for 24 hours to obtain solid cellulose nanocrystals.

[0087] According to the calculation method of cellulose nanocrystal yield, the cellulose nanocrystal yield obtained in Example 8 was 56.38%, which was 9.12% higher than that of cellulose nanocrystals not treated with PEF.

[0088] Calculation method for cellulose nanocrystal yield:

[0089] The nanocellulose suspension was evenly dispersed, the total volume was determined, 25 mL was measured in a weighing bottle, and vacuum freeze-dried until the mass was constant. The yield of nanocellulose was calculated as follows:

[0090]

[0091] Wherein: Y is the yield of cellulose nanocrystals, %; m1 is the total mass of the sample and the weighing bottle after drying, g; m2 is the mass of the weighing bottle, g; m is the mass of cellulose powder, g; V is the total volume of the cellulose nanocrystal suspension, mL.

[0092] The present invention obtains the scanning electron microscope image of cellulose powder by evenly pasting a small amount of sample powder with conductive double-sided adhesive, pasting it on a stage, marking it with a serial number and then directly performing gold spraying treatment, and finally taking pictures and observing each sample using a scanning electron microscope.

[0093] Determination of carboxyl content:

[0094] Accurately weigh 0.054 g of the completely acidified sample and place it in a 20 mL headspace test bottle. Add 4.0 mL of 0.08 mol·L -1 NaHCO3 solution. Shake the test bottle to fully disperse the sample, perform headspace gas chromatography test, and record the area (A) of the carbon dioxide gas chromatographic peak.

[0095] Determination of the correction factor: Add 4.0 mL of 0.08 mol·L -1 0, 10, 20, 30, 40, and 50 μL of NaHCO3 solution with a concentration of 0.01 mol·L were added to the sealed headspace sample bottle. -1 Hydrochloric acid solution (repeated 3 times), headspace gas chromatography detection, and obtain the peak area of ​​their chromatogram signals respectively. Then, the absolute amount of hydrochloric acid added to the headspace sample bottle (mol) is used as the abscissa, and the peak area of ​​the corresponding chromatogram signal is used as the ordinate to draw a standard curve. The slope of the obtained standard curve is the correction coefficient k. The carboxyl content is calculated by the formula:

[0096]

[0097] Where: C COOH is the content of carboxylic acid groups in the sample to be tested (mmol·g -1 ); A is the peak area of ​​carbon dioxide signal detected after adding sample; A0 is the peak area of ​​carbon dioxide signal detected when no sample is added; k is the calibration constant (mmol -1 ); m is the absolute dry mass of the sample (g).

[0098] Figure 1 The cellulose nanocrystal yields of Comparative Example 1, Comparative Example 2 and Examples 2, 5, 7, and 8 are shown in Figure 1. The results show that the yield of Comparative Example 1 as a control group without pulsed electric field treatment is 51.67%. With the increase of electric field strength, the yield of cellulose nanocrystals shows a trend of first increasing and then decreasing. The highest is Example 5, which reaches 64.45% when the electric field strength is 15 kV / cm. The lowest is Comparative Example 2, which has a yield of 48.77% when the electric field strength is 30 kV / cm, which is even 5.61% lower than that of cellulose nanocrystals without PEF treatment. This shows that pulsed electric field treatment with appropriate field strength can significantly increase the yield of cellulose nanocrystals. At the same time, too high electric field strength will lead to excessive degradation of cellulose. The subsequent oxidation reaction will decompose cellulose into monosaccharide units, thereby reducing the yield of nanocrystals.

[0099] Figure 2 The scanning electron microscope images of cellulose powders of Examples 5, 7 and Comparative Example 1 are shown. As can be seen from the figure, the surface of Comparative Example 1, which is a cellulose powder not treated with a pulse electric field, is the smoothest, arranged in an orderly manner in long strips, and has fewer cracks. The surface of Example 5 becomes rough and wrinkled, with more cracks. The surface of Example 7 is severely deformed, and the cellulose structure is destroyed. It can be seen that the treatment of the pulse electric field can change the surface structure of the cellulose powder, increase the accessibility of the cellulose molecules, and facilitate the subsequent oxidation reaction.

[0100] Figure 3The carboxyl content of cellulose nanocrystals in Comparative Example 1 and Comparative Example 2 and Examples 2, 5, and 7 is shown in the figure. As can be seen from the figure, the carboxyl content of Comparative Example 1 without pulse electric field treatment is the lowest at 1.27 mmol·g -1, The carboxyl content of Comparative Example 2 and Examples 2, 5, and 7 treated with a pulse electric field was significantly increased, and reached a maximum of 2.01 mmol·g in Example 7 at an electric field strength of 20 kV / cm. -1 This indicates that after the pulse electric field treatment, the specific surface area of ​​cellulose increases, the reaction with APS is more complete, and more hydroxyl groups are oxidized to carboxyl groups.

Claims

1. A method for preparing cellulose nanocrystals by using pulsed electric field-assisted ammonium persulfate oxidation, characterized in that: Using bleached fiber pulp as a substrate, carboxylated cellulose nanocrystals are prepared by pulse electric field treatment and APS oxidation. The method specifically includes the following steps: (1) crushing a bleached fiber pulp sheet to obtain cellulose powder; (2) adding ammonium persulfate APS into water and dissolving it to form an ammonium persulfate APS aqueous solution; (3) preparing a suspension of cellulose powder with deionized water at a solid-liquid ratio of 1:50-1:100 g / ml, stirring evenly, connecting a peristaltic pump, adjusting the flow rate and removing bubbles, allowing the sample to fully flow through the pulse electric field treatment chamber, performing pulse electric field treatment, and then filtering and drying to obtain treated cellulose; the pulse electric field treatment conditions are: field strength 10-30 kV / cm, frequency 50-300 Hz, pulse width 8-12 μs, and treatment time 5-20 min; (4) adding the treated cellulose into an aqueous solution of ammonium persulfate (APS) to allow for sufficient reaction; (5) The suspension after the reaction is washed to neutrality by centrifugation to separate the cellulose nanocrystal dispersion, which is then freeze-dried to obtain solid cellulose nanocrystals.

2. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (1), the bleached fiber pulp board is one or more of microcrystalline cellulose, bleached bagasse pulp, bleached lychee peel pulp, bleached wood pulp, bleached straw pulp, bleached cotton pulp, and bleached bamboo pulp.

3. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (1), the bleached fiber pulp is crushed and passed through a 200-mesh sieve to obtain cellulose powder.

4. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (2), the mass percentage concentration of the ammonium persulfate APS aqueous solution is 15% to 21%.

5. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (3), the material-liquid ratio is 1:60-1:80 g / ml.

6. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (3), the flow rate of the peristaltic pump is 200-300 ml / min.

7. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (3), the pulse electric field treatment conditions are: field strength 10-25 kV / cm, frequency 200-300 Hz, pulse width 8-10 μs, and treatment time 10-15 min.

8. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (4), the reaction time is 10 to 16 hours, and the reaction temperature is 55° C. to 90° C.

9. The method for preparing cellulose nanocrystals by pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (5), the centrifugal speed is 6000-7000 rpm / min.

10. The method for preparing cellulose nanocrystals by using pulsed electric field-assisted ammonium persulfate oxidation according to claim 1, characterized in that: In step (5), the washing is performed by repeatedly adding deionized water and centrifuging until the mixture becomes neutral.

Citation Information

Patent Citations

  • Aminated nano cellulose crystal and preparation method thereof

    CN105646722A

  • Preparation method of environment-friendly edible food packaging film

    CN105968826A

  • A preparing method of cob nanometer cellulose

    CN107556392A

  • Method for preparing carboxylated nanocellulose by hydrolyzing citric acid under high-pressure condition

    CN111072786A

  • Spherical nanocrystalline cellulose based on furfural residues and preparation method thereof

    CN114874343A